2011
DOI: 10.1016/j.contraception.2011.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Duration of use of a levonorgestrel IUS amongst nulliparous and adolescent women

Abstract: Background Intrauterine devices (IUDs) are cost-effective if used for two or more years. Early discontinuation may lead to reduced cost-effectiveness of this method and unintended pregnancy if other contraceptives are not used. This study sought to examine rates and reasons for discontinuation of IUS use in adolescents versus older women and nulliparous versus parous women, as these groups may be more likely to discontinue use. Study Design Retrospective cohort study of women receiving a levonorgestrel IUS b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 18 publications
1
29
0
1
Order By: Relevance
“…In the USA, the recommended patient profile for the LNG-IUS includes 'women who have had at least one child' -however, such general restrictions regarding use in nulliparous women are not in place in the countries where the LNG-IUS is marketed the most. Adolescents and nulliparous women are not more likely to prematurely discontinue use of their IUS than adult or parous women [86]. Recent studies have confirmed that the LNG-IUS can also be used for reduction of dysmenorrhea and HMB by young and nulliparous women (Table 2).…”
Section: The Use Of the Lng-ius In Nulliparous Womenmentioning
confidence: 76%
See 3 more Smart Citations
“…In the USA, the recommended patient profile for the LNG-IUS includes 'women who have had at least one child' -however, such general restrictions regarding use in nulliparous women are not in place in the countries where the LNG-IUS is marketed the most. Adolescents and nulliparous women are not more likely to prematurely discontinue use of their IUS than adult or parous women [86]. Recent studies have confirmed that the LNG-IUS can also be used for reduction of dysmenorrhea and HMB by young and nulliparous women (Table 2).…”
Section: The Use Of the Lng-ius In Nulliparous Womenmentioning
confidence: 76%
“…Despite the fact that the insertion was experienced as painful by a large proportion of women, this did not negatively influence satisfaction with the LNG-IUS [80]. Compared with 'older' women or parous women, young or nulliparous women were not more likely to have their IUS removed because of dissatisfaction (Table 2) [86]. The most common reason for removing the IUS was wish for pregnancy.…”
Section: The Use Of the Lng-ius In Nulliparous Womenmentioning
confidence: 99%
See 2 more Smart Citations
“…The main drawback of the progestogen implant is frequent and/or prolonged breakthrough bleeding, resulting in a comparable and meaningful fraction (20-25%) of adolescents and adults requesting early removal [8]. Rapidly accumulating experience with IUCDs in adolescents shows that expulsion rates are slightly higher than the~5% incidence rate in parous women, whereas the continuation rate and satisfaction are comparable in both groups, particularly with the progestogen-containing IUCD [1]. Abnormal bleeding (frequent, prolonged and/or abundant) and pelvic pain or cramps are potential IUCD side effects yet appear to be more common with copper IUCDs.…”
Section: Contraceptive Choices For Adolescentsmentioning
confidence: 85%